Low back pain patients' perspectives on long-term adherence to home-based exercise programmes in physiotherapy. (December 2018) - Saner, Jeannette; Bergman, Esther M.; de Bie, Rob A.; Sieben, Judith M.
Abstract: Background: Adherence to an exercise programme impacts the outcome of physiotherapy treatment in patients with non-specific low back pain. Objectives: The aim of this study was to explore the patients' perspectives on long term adherence to such exercise programmes. Design: This qualitative study was embedded in a randomised controlled trial (RCT) which compared the effectiveness of two types of exercise programme on patients with nonspecific low back pain. Methods: Answers from 44 participants to three open-ended questions were analysed using thematic analysis. Results/findings: Patients' perceptions related to the following themes: 1) the role of knowledge in long-term exercise adherence; 2) strategies to support exercise adherence; 3) barriers to exercise adherence 4) the role of perceived effects of exercise. Conclusions: Adherence to long-term exercise is supported through knowledge of the exercises and correct performance. A self-initiated training strategy is the most successful in the perception of participants. Individually supervised physiotherapy treatment that includes coaching towards strategies for post-treatment long term exercise behaviour is recommended. Highlights: Long term adherence to exercise in patients with low back pain needs careful coaching strategies in physiotherapy treatment. Improved self-confidence through specific and individual instructions influenced the adherence. The perceived positive association between exercise and pain reduction helped to overcome barriers. Stimulating a combination of the recommended exercises with a self-initiated physical training improves performance.